Changes in habitat use patterns by bottlenose dolphins over a 10‐year period render static management boundaries ineffective. Issue 5 (8th May 2014) - Hartel, Elizabeth F.; Constantine, Rochelle; Torres, Leigh G.
ABSTRACT Bottlenose dolphins (Tursiops truncatus) in northern New Zealand range widely and their coastal distribution increases their risk of exposure to a variety of threats. Marine protected areas (MPAs) are increasingly used to protect species but there is a paucity of studies examining their efficacy. In the Bay of Islands, New Zealand (35°14'S, 174°06'E), dolphin distribution and habitat use patterns were examined between two time periods: 1996–2000 and 2007–2010. In addition, dolphin use of tourism exclusion zones designed to protect the dolphins were assessed. Spatial distribution was analysed using kernel densities and Mantel tests. Broad‐scale distribution patterns remained constant between the two periods but fine‐scale dolphin distribution patterns shifted considerably. The exclusion zones that were established based on results from the 1996–2000 study were rarely used in 2007–2010, and therefore no longer provided dolphins protection from tourism. This research demonstrates the plasticity in dolphin habitat use patterns through time and the importance of re‐evaluating the efficacy of static protected areas, especially for wide‐ranging species. Copyright © 2014 John Wiley & Sons, Ltd.